2006
DOI: 10.4000/aaa.1316
|View full text |Cite
|
Sign up to set email alerts
|

Origin disputed. The making, use and evaluation of Ghanaian textiles

Abstract: Depuis les années 1990, un vif débat a pris forme au Ghana sur l’origine du kente. Les discussions portent principalement sur l’antériorité du tissage Asante sur le tissage Ewe. Cette acitvité est très ancienne dans de nombreuses régions du Ghana, et les relations entre les régions de parler Ewe et celles de parler Twi remontent aussi loin que le xixe s. au moins. Cet article vise à déméler et à mettre en évidence de quelle manière revendications et appropriations de l’origine du kente sont localement répétés … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…They only suggest that weaving possibly originated independently in the two areas of Ashanti and Ewe in Ghana. This finding validates the view of Kraamer [36] who indicated that it is neither the Asante nor the Ewe who taught the other group how to weave.…”
Section: The Development Of Kete Weaving As a Vocation In The Agortime Traditional Areasupporting
confidence: 87%
“…They only suggest that weaving possibly originated independently in the two areas of Ashanti and Ewe in Ghana. This finding validates the view of Kraamer [36] who indicated that it is neither the Asante nor the Ewe who taught the other group how to weave.…”
Section: The Development Of Kete Weaving As a Vocation In The Agortime Traditional Areasupporting
confidence: 87%
“…The traditional authorities of two kente weaving towns of Agotime-Kpetoe and Bonwire have instituted annual kente festivals in honor of kente. The Agotime Kente festival, also known in Ewe as Agbamevorza, started in 1996 and the Bonwire Kente festival started in 1998 [23]. The aim of the Agotime Kente festival is to preserve the cultural and aesthetic values of the kente cloth, display uses of kente cloth and expose innovations and techniques in kente industry among other objectives to address the developmental needs of the Agotime traditional area (available online: http://ewekente.com/home, accessed on 16 December 2018).…”
Section: Kente Weaving In Ghanamentioning
confidence: 99%
“…especially lettehng and crosses in single strips or stoles (in the first instance developed for the African American market but now also widely used within Ghana) has its roots with Ewe weavers who attended the NMG missionary schools. For an in-depth discussion of the development of Asante and Ewe textile traditions and their interrelationships, see Kraamer 2005aKraamer , 2005bKraamer , 2006aKraamer , 2006bRoss 1998.…”
Section: Hand-woven Textiles and Christian Worshipmentioning
confidence: 99%